Prognostic Assessment of Endocrine Disturbances in Posttraumatic Subarachnoid Hemorrhage - Agrawal, Manish; Varshney, Tarun; Sinha, Virendra Deo (Indian Journal of Neurotrauma, 2017)
Traumatic subarachnoid hemorrhage (SAH) is a condition with high risk for the development of hypopituitarism. Hormonal assessment is not a part of routine assessment after traumatic SAH. This study is a prospective screening study from our center focusing on the prognostic assessment of endocrine disturbances in posttraumatic SAH. A total of 150 consecutive patients with head injuries with SAH were included irrespective of their age and sex. Patients were divided into three groups: with normal hormonal status (group 1), patients with endocrine disturbances with no hormonal replacement (group 2), and patients with endocrine disturbances with replacement therapy (group 3). Hormonal assessment was done within 24 hours of admission and repeated at 7 to 15 days and at 1-month interval. Most commonly affected was pituitary-thyroid axis, and the most common hormone to increase was cortisol. In group 3, a statistically significant improvement was seen in Glasgow outcome score (GOS) as compared with the other two groups at 1 month. A statistically significant positive correlation has been found between thyroxine (T4) at 30 days and Glasgow coma scale (GCS) at discharge in group 3, a negative correlation has been found between GCS at admission and serum cortisol at days 7 to 15 in group3. A positive correlation has been found between GCS at admission and GOS at 1 month in group 3. The authors have demonstrated evidence of pituitary dysfunction following traumatic brain injury (TBI) with SAH. Patients with traumatic SAH should be screened for hypopituitarism, so that appropriate hormone replacement is given to improve the outcome of these patients.
Keywords: head injury; subarachnoid hemorrhage; endocrine dysfunction; hormone replacement